Heat Transfer of Alumina Sands in Fluidized Bed Combustor with Novel Circular Edge Segments Air Distributor - Ahmmad Shukrie, Md Yudin; Shahrani, Anuar; Azri, Alias (Elsevier Ltd, 2015)
Fluidized bed combustor, which consists of a reaction chamber, an air distribution plate, uses inert particles, as its bed material. In order to ensure stable operation, it is apparent that the operating velocity of the air should be sufficiently large so that the flow rate through it is relatively undisturbed by the bed pressure fluctuation above it. However, high distributor pressure drop in fluidized bed system is undesirable because it will lead to high energy input in the blower to supply the fluidization air to fluidize the inert sand particles. Thus, the new novel designs of air distributor that consists of circular edge segments that contributed to low pressure drop and improvement of heat and mass transfer in fluidized bed combustor is introduced and will become primary interest of this research. The effects of temperature variations between an electrically heated tube immersed vertically in fluidized bed and alumina particles of various sizes were experimentally studied. In this paper, the data for heat transfer coefficient for an electrically heated vertical tube immersed vertically in fluidized bed combustor consists of alumina particles diameter ranging from (Full-size image (10 K)= 100, 177 and 250 μm) is reported at temperature from 50 oC to 250 oC.